Glimmer : a story of survival, hope, and healing - Murphy, Kimberly Shannon; Field, Genevieve (Harper Wave, an imprint of HarperCollinsPublishers, 2023)
A memoir from one of the most successful stuntwomen in Hollywood chronicles her path to recovery from a childhood of sexual abuse and offers hope for others who have suffered through the same ordeal.